1992
DOI: 10.3171/jns.1992.76.1.0023
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone or naloxone treatment after acute spinal cord injury: 1-year follow-up data

Abstract: The 1-year follow-up data of a multicenter randomized controlled trial of methylprednisolone (30 mg/kg bolus and 5.4 mg/kg/hr for 23 hours) or naloxone (5.4 mg/kg bolus and 4.0 mg/kg/hr for 23 hours) treatment for acute spinal cord injury are reported and compared with placebo results. In patients treated with methylprednisolone within 8 hours of injury, increased recovery of neurological function was seen at 6 weeks and at 6 months and continued to be observed 1 year after injury. For motor function, this dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
293
0
20

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(318 citation statements)
references
References 45 publications
(1 reference statement)
5
293
0
20
Order By: Relevance
“…Three large, double-blind, placebocontrolled pharmaceutical trials focussed on acute neuroprotection and rehabilitation in SCI are reported in the literature; the National Acute Spinal Cord Injury Study (NASCIS), Sygen and GK-11 trials. [2][3][4][5][6][7][8] The data from the placebo-control groups in these studies allow the natural history of recovery from injury to be examined within the context of a randomized controlled trial (RCT). In addition, there have been a number of studies of long-term outcomes after SCI that provide valuable information on expected recovery rates, [10][11][12] as well as some recently unpublished data from the European Multicenter study in Spinal Cord Injury (EMSCI).…”
Section: Sources Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Three large, double-blind, placebocontrolled pharmaceutical trials focussed on acute neuroprotection and rehabilitation in SCI are reported in the literature; the National Acute Spinal Cord Injury Study (NASCIS), Sygen and GK-11 trials. [2][3][4][5][6][7][8] The data from the placebo-control groups in these studies allow the natural history of recovery from injury to be examined within the context of a randomized controlled trial (RCT). In addition, there have been a number of studies of long-term outcomes after SCI that provide valuable information on expected recovery rates, [10][11][12] as well as some recently unpublished data from the European Multicenter study in Spinal Cord Injury (EMSCI).…”
Section: Sources Of Datamentioning
confidence: 99%
“…When no difference in functional outcome was seen, the ethical hurdle was reduced and the second trial compared three groups: placebo, 23 h methylprednisolone treatment, and naloxone. Patients were examined on admission to hospital emergency room, mostly within 12 h after injury, and an average time from injury to treatment of 8.9 h. In this second study, 2,3 487 patients were enrolled, of whom 171 were in the placebo group, and outcomes measured at 6 weeks, 6 months and 1 year. The third NASCIS study 4,5 did not have a placebo-control group, because following its apparent efficacy in the NASCIS II study it was considered that to deny some form of methylprednisolone treatment would be unethical.…”
Section: Sources Of Datamentioning
confidence: 99%
“…This paper addresses the following ques tions for four liver enzymes: (1) Do either MPSS or NAL compared to placebo bring about significant changes in liver enzymes? (2) Is there any impact on the liver from the spinal cord injury itself?…”
Section: Introductionmentioning
confidence: 99%
“…Based on this "neuroprotective" strategy, the first and only treatment to date that has demonstrated a significant improvement in neurological recovery, in a multicenter, randomized, placebo-controlled clinical trial in human SCI, has been high-dose methylprednisolone (MP) (National Acute Spinal Cord Injury Study II) [1][2][3]. This landmark trial was inspired by the multiple studies carried out in the 1980s by Hall, Braughler, Anderson, and Means in cat SCI models.…”
mentioning
confidence: 99%
“…They documented the ability of high-dose MP, intravenously administered, to protect the contused or compressed spinal cord, together with the inhibition of oxygen free radical-induced lipid peroxidation (see review by Hall and Springer [4]). Although, the National Acute Spinal Cord Injury Study II trial and its interpretation have been repeatedly critiqued since its publication in the early 1990s [1][2][3] and the risk-to-benefit ratio of high-dose MP treatment has been questioned, the fact remains that it represents the only available acute neuroprotective treatment for SCI, and its modest level of protective efficacy has continued to inspire the search for safer and more effective acute treatment approaches. In that regard, this issue of Neurotherapeutics contains multiple articles that review promising neuroprotective mechanistic avenues, some of which are moving toward clinical translation.…”
mentioning
confidence: 99%